Defining metrics of the Quasi-Biennial Oscillation in global climate models - Schenzinger, V; Osprey, S; Gray, L; Butchart, N (Copernicus Publications, 2016)
As the dominant mode of variability in the tropical stratosphere, the Quasi-Biennial Oscillation (QBO) has been subject to extensive research. Though there is a well developed theory of this phenomenon being forced by wave-mean flow interaction, simulating the QBO adequately in global climate models (GCMs) still remains difficult. This paper presents a set of metrics to characterise the QBO using a number of different reanalysis datasets and the FU Berlin radiosonde observation dataset. The same metrics are then calculated from CMIP5 and CCMVal-2 intercomparison project simulations which included a representation of QBO like behaviour to evaluate which aspects of the QBO are well captured by the models and which ones remain a challenge for future model development.